Analisis Kemampuan Kognitif Penghafal Al-qur’an Dalam Menyelesaikan Soal Matematika - indah rahayu; Murtafiatul Walidah; Aswar Anas (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2026)
The study aims to analyze the cognitive abilities of students who memorize the Qur'an in solving mathematics problems on the subject of Two-Variable Linear Equation Systems (SPLDV). The study uses a descriptive approach with five students who memorize the Qur'an at MTs. Wahid Hasyim, who has memorized between 1 and 5 juz. Data were collected through written tests, semi-structured interviews, observations, and documentation, then analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the students' cognitive abilities were in the good category with an average mastery of 73%. The indicator of understanding problems achieved the highest score (82%), followed by constructing mathematical models (76%), solving problems (70%), and evaluating results (65%). The findings show that tahfiz activities contribute to students' focus, memory, and regularity of thinking, especially in the stages of understanding problems and formulating mathematical models, although procedural and evaluative abilities need to be improved. This study provides an initial overview of the potential for integrating tahfiz activities with mathematics learning to support the development of students' cognitive abilities. Keywords: cognitive ability, Qur’an memorization